Supervisi Akademik Kepala Madrasah Dalam Meningkatkan Kompetensi Profesional Guru (Studi Multi Kasus Madrasah Aliyah Negeri Kabupaten Pati) (Pascasarjana IAIN Kudus, 2020)
Penelitian ini dilatarbelakangi kurang optimalnya kegiatan Kepala Madrasah dalam mensupervisi guru. Penelitian ini bertujuan untuk menjawab permasalahan: (1) bagaimana pelaksanaan supervisi akademik oleh Kepala Madrasah, (2) bagaimana faktor pendukung kegiatan Supervisi Akademik dan hambatannya, serta (3) bagaimana peran Kepala Madrasah sebagai supervisor. Penelitian ini mengikuti model studi multi kasus, dengan pendekatan kualitatif deskriptif. Berlokasi di MAN 1 Pati dan MAN 2 Pati. Hasil penelitian menunjukkan: (1) pelaksanaan Supervisi Akademik meliputi tiga kegiatan, yaitu perencanaan program (b) strategi Supervisi Akademik, (c) evaluasi menggunakan instrumen penilaian baku mengacu aturan Kementerian Agama, dengan tindak lanjut memberikan penguatan dan penghargaan serta pembinaan dan pelatihan. (2) Faktor-faktor pendukung meliputi jadwal supervisi akademik, kesediaan guru disupervisi, sikap guru senior yang kooperatif, kelengkapan administrasi pembelajaran, kontinyuitas pelaksanakan Supervisi Akademik. Faktor-faktor penghambat terdiri dari keterbatasan waktu Kepala Madrasah dan guru, beban guru mengajar yang tidak sesuai dengan latar belakang Pendidikan (3) Peran Kepala Madrasah sebagai Supervisor memiliki kompetensi: merencanakan program, melaksanakan dan melakukan evaluasi serta menindaklanjuti hasil Supervisi Akademik.This research is motivated by the less optimal activities of the Madrasah Head in supervising teachers. This study aims to answer the problem:(1) how the implementation of academic supervision by the Head of Madrasa (2) how the factors supporting Academic Supervision activities and their obstacles, and (3) how the role of the Madrasah Head as a supervisor. This research follows a multi-case study model, with a descriptive qualitative approach. Located in MAN 1 Pati and MAN 2 Pati. The results showed: (1) Implementation of Academic Supervision includes three activities, namely: (a) program planning, (b) Academic Supervision strategy, and (c) evaluation using standard assessment instruments referring to the rules of the Ministry of Religion, with follow-up giving reinforcement and appreciation as well as coaching and training. (2) Supporting factors include the schedule of academic supervision, the willingness of supervised teachers, fellow teaching professions, the attitude of the cooperative senior teachers, completeness of the administration of learning, continuity of the Madrasah Head in carrying out Academic Supervision. The inhibiting factors consist of the limited time of the Madrasah Head and the teacher, the burden of the teacher teaching that is not following the educational background. (3) The Role of the Madrasah Head as a Supervisor has competence: planning programs, implementing and evaluating, and following up on Academic Supervision results. Implementation of Academic Supervision includes three activities, namely: (a) program planning, (b) Academic Supervision strategy by setting targets focused (c) evaluation using standard assessment instruments. (2) Supporting factors. (3) The Role of the Madrasah Head as a Supervisor has competence.